2016
DOI: 10.1097/md.0000000000003839
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical outcome of transthoracic esophagectomy with thoracic duct resection

Abstract: The number of dissected lymph nodes (LNs), surgical outcomes, and postoperative recurrence-free survival (RFS) were compared between thoracic duct (TD)-preserved and TD-resected groups. The distribution of metastasis in LNs around TD (TDLN) was reviewed. Transthoracic esophagectomy (TTE) with TD resection for esophageal cancer patients has been one of the standard procedures. Because the adipose tissue surrounding the TD contains LNs, TD resection might be necessary for radical LN dissection. However, few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 13 publications
5
16
0
Order By: Relevance
“…The current study successfully validated our previous findings that there was the existence of LN metastasis around the TD in ESCC. 16 Subsequently, we further confirmed that TDLN metastasis occurred In contrast to the value of TDLN metastasis as a prognostic indicator, the efficacy of lymphadenectomy of TDLN with TD resection might not be remarkable. Based on the current study, which the first study evaluating the prognosis of patients with TDLN metastasis for each location, the incidence rate of TDLN metastasis was relatively low, and its prognosis was proven to be extremely poor.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The current study successfully validated our previous findings that there was the existence of LN metastasis around the TD in ESCC. 16 Subsequently, we further confirmed that TDLN metastasis occurred In contrast to the value of TDLN metastasis as a prognostic indicator, the efficacy of lymphadenectomy of TDLN with TD resection might not be remarkable. Based on the current study, which the first study evaluating the prognosis of patients with TDLN metastasis for each location, the incidence rate of TDLN metastasis was relatively low, and its prognosis was proven to be extremely poor.…”
Section: Discussionsupporting
confidence: 54%
“…As previously reported, since June 2013, the TDLN has been examined independently of paratracheal and aortic LNs in our institution. 16 All patients who underwent TTE with TD resection for esophageal malignancies at the Keio University Hospital between June 2013 and December 2019 were reviewed. We excluded patients with a cT4 tumor, adenocarcinomas, patients that underwent salvage esophagectomy after definitive chemoradiotherapy, and those with R2 resection.…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Regarding whether to resect the thoracic ducts or preserve them in oesophageal resection, there have been few reports on the efficacy of thoracic duct resection [8], and a consensus of resection of thoracic duct has yet to be reached. In our hospital, we usually clip and dissect the thoracic duct at the level above the diaphragm for oesophageal cancer; however, postoperative chylothorax still remains a rare complication.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the present study, there have been hardly any reports showing the effectiveness of etilefrine in cases of chylothorax after esophagectomy with TDR [ 12 ]. In surgery for esophageal cancer, the thoracic duct is resected to ensure thorough removal of the lymph nodes around the thoracic duct, and the oncological effectiveness of TDR has been demonstrated [ 13 , 14 ]. In performing TDR, we double-clip the thoracic duct above the diaphragm in patients with cStage II or more advanced esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%